Examining Prevalence and Risk Factors of Hepatitis B Virus Among Pregnant Women in the Context of Prevention of Mother-To-Child Transmission - Asamoah, Andrews; Saho, Prosper (British Journal of Healthcare and Medical Research, 2024)
Background: Hepatitis B. virus continues to pose threat to human by infecting millions of people globally through the liver and remains a public health problem even though there has been the availability of HB vaccine and antiviral agents over the years. It is estimated that 240 million people worldwide are chronically infected, particularly in low and middle-income countries (LMICs). The major well-established risk of harm associated with maternal HBV infection is perinatal transmission to the infant occurring most commonly through the process of delivery. Objective: The aim of this study is to estimate the prevalence of Hepatitis B and associated risk factors among pregnant women in Ejura-Sekyedumase Municipal. Method: The study adopted a cross sectional approach to research design among pregnant women attending antenatal care. Proportion sampling method was applied to each facility based on the number of pregnant women attending ANC clinic to determine the number of pregnant women to be interviewed from each facility. Statistical analysis was done using STATA and results were presented in frequencies and percentages while regression analysis results was report in odds ratio with its associated chi-square and p-values. Results: Three hundred and thirteen pregnant women participated in the study with a mean age of 30.3 +2.5. A total of 64 pregnant women tested positive for HB virus, giving a prevalence rate of 20.5%. Factors that were significantly associated with HB virus infection among pregnant women include age 18-24 and 45+ years, polygamous marriage, blood transfusion and multiple sexual partners. About 49% of the pregnant women had adequate knowledge on hepatitis B infection. Knowledge on hepatitis B infection was significantly associated with age, religion, place of residence and place of past deliveries. Conclusion: With the high prevalence of hepatitis B among pregnant women in the district, it is important urgent actions are taking to address the root causes of the high infection among the pregnant women. Screening and HBV vaccine introduction should be key on the agenda among policy-makers.